Climate warming causes photobiont degradation and carbon starvation in a boreal climate sentinel lichen. Issue 2 (13th February 2023) - Meyer, Abigail R.; Valentin, Maria; Liulevicius, Laima; McDonald, Tami R.; Nelsen, Matthew P.; Pengra, Jean; Smith, Robert J.; Stanton, Daniel
Abstract: Premise: The long‐term potential for acclimation by lichens to changing climates is poorly known, despite their prominent roles in forested ecosystems. Although often considered "extremophiles, " lichens may not readily acclimate to novel climates well beyond historical norms. In a previous study (Smith et al., 2018), Evernia mesomorpha transplants in a whole‐ecosystem climate change experiment showed drastic mass loss after 1 yr of warming and drying; however, the causes of this mass loss were not addressed. Methods: We examined the causes of this warming‐induced mass loss by measuring physiological, functional, and reproductive attributes of lichen transplants. Results: Severe loss of mass and physiological function occurred above +2°C of experimental warming. Loss of algal symbionts ("bleaching") and turnover in algal community compositions increased with temperature and were the clearest impacts of experimental warming. Enhanced CO2 had no significant physiological or symbiont composition effects. The functional loss of algal photobionts led to significant loss of mass and specific thallus mass (STM), which in turn reduced water‐holding capacity (WHC). Although algal genotypes remained detectable in thalli exposed to higher stress, within‐thallus photobiont communities shifted in composition toward greater diversity. Conclusions: The strong negative impacts of warming and/or lower humidity on Evernia mesomorpha were driven by a loss of photobiont activity. Analogous to the effects of climate change on corals, the balance of symbiont carbon metabolism in lichens is central to their resilience to changing conditions.